Synthesis of Chalcones as Potential α‐Glucosidase Inhibitors, In‐Vitro and In‐Silico Studies. Issue 37 (1st October 2021) - Mukhtar, Asma; Shah, Shazia; Kanwal,; Khan, Khalid Mohammed; Khan, Shahid Ullah; Zaib, Sumera; Iqbal, Jamshed; Parveen, Shahnaz; Taha, Muhammad; Hussain, Shafqat; Hameed, Shahryar; Khan, Naveed Ahmed; et al.
Abstract: α‐glucosidase inhibitors are potential antihyperglycemic agents. Seventeen chalcones derivatives (1 –17 ) were synthesized by reactions of diversely substituted aldehydes with various ketones. The structures of compounds were characterized by using nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS) and carbon, hydrogen, nitrogen (CHN) analysis. These synthetic molecules were tested for α ‐glucosidase inhibitory activity. Acarbose was used as a standard drug and positive control in this study which exhibited an IC50 of 2.91±0.02 μ M. Of seventeen, nine molecules 1 ‐3, 5, 6, 8, and 11 ‐13 displayed significant inhibition with IC50 values 1.19±0.19 to 15.79±0.99 μ M. Compound 6 ( E )‐3‐(3, 5‐dichloro‐2‐hydroxyphenyl)‐1‐( p ‐tolyl)prop‐2‐en‐1‐one with hydroxy and chloro substitutions was found to be the most active compound and a novel compound of this library with IC50 =1.19±0.19 μ M. Active molecules were subjected to in silico study to determine binding interactions with target site of α ‐glucosidase. Abstract : Chalcones are important lead compounds for glycoside hydrolases activity. Seventeen chalcones derivatives were synthesized from different substituted acetophenone and aldehydes in this study. These compounds were found to exhibit α ‐glucosidase inhibition and have the potential to treat diabetes related complications such as listed in the figure below. Out of the seventeen compounds tested, compound 6 with hydroxy and chloro substitutions was found to be the most effective with IC50 =1.19±0.19 μM.